(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Managing electronic systems is challenging due to the need for compact and efficient thermal solutions. Make sure to scale appropriately to avoid any failures that may occur due to the development of hot spots. Using high-performance heat sinks can improve the efficiency and reliability of the system. Enhancing the effi-ciency of heat transfer can significantly improve the previously low coefficient of performance (COP) of ther-moelectric cooling and heating. Research is constantly being conducted to enhance its effectiveness through the reduction of the thermal boundary layer thickness and the increase of the heat transfer surface area. Perfora-tions in the fins are a method that can be used to enhance its effectiveness. Studies have demonstrated that circular perforations can reduce temperature from 300°C to 38°C, compared to 55°C for solid fins. Further-more, the positioning of perforations on the fins, specifically at the upper section, has been highlighted to im-prove thermal efficiency. Perforated fins, especially those with circular shapes, can improve heat transfer coef-ficients and promote uniform temperature distributions on the surfaces of the fins. This eventually optimises the thermal efficiency of heat sinks.